2014
DOI: 10.1523/jneurosci.2935-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Upregulates ATP Binding Cassette Transporter Expression and Activity at the Blood-Brain and Blood-Spinal Cord Barriers

Abstract: Activation of nuclear factor E2-related factor-2 (Nrf2), a sensor of oxidative stress, is neuroprotective in animal models of cerebral ischemia, traumatic brain injury, subarachnoid hemorrhage, and spinal cord injury. We show here that Nrf2 activation with sulforaphane (SFN) in vivo or in vitro increases expression and transport activity of three ATP-driven drug efflux pumps at the blood-brain barrier [P-glycoprotein, ATP binding cassette b1 (Abcb1); multidrug resistance-associated protein-2 (Mrp2), Abcc2; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(106 citation statements)
references
References 42 publications
(36 reference statements)
2
101
0
3
Order By: Relevance
“…(Figures 2B&C). As shown in our previous publications, NFkB is a nuclear transcription factor known to induce P-gp expression in rat brain capillaries [23]. Using immunohistochemistry, we observed no significant difference of NFkB nuclear localization in brain and spinal cord capillaries from SOD rats compared among all three ALS stages (Figure 2D).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…(Figures 2B&C). As shown in our previous publications, NFkB is a nuclear transcription factor known to induce P-gp expression in rat brain capillaries [23]. Using immunohistochemistry, we observed no significant difference of NFkB nuclear localization in brain and spinal cord capillaries from SOD rats compared among all three ALS stages (Figure 2D).…”
Section: Resultssupporting
confidence: 77%
“…Next, we examined the role of NFÎșB for P-gp induction in SOD rats, because this transcription factor was shown to increase P-gp at the rat BBB [23] and was recently shown to play a role in microglia-induced motor neuron death in an ALS mouse model with SOD1-G93A mutation [10]. We observed no major changes of NFÎșB nuclear localization in capillaries of the brain and spinal cords from SOD rats at all ALS stages compared to wildtype.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we previously showed that the blood-spinal cord barrier is similar to the blood-brain barrier with respect to ABC transporter expression and regulation by ligandactivated transcription factors, such as, PXR, CAR, AhR, and Nrf2/p53 Wang et al, 2014). Using mouse spinal cord capillaries, we found that basal P-glycoprotein transport activity was regulated by the same signaling pathway described in brain capillaries (Cartwright et al, 2013).…”
Section: P-glycoproteinmentioning
confidence: 75%
“…The majority of these studies focused on the mechanisms of xenobiotic-induced upregulation of MRP2, indicating that diesel exhaust particles can induce MRP2 expression and that the pregnane X receptor, the constitutive androstane receptor, the farnesyl X receptor, and the activation of the transcription factor NF-E2-related factor-2 (Nrf2) can contribute to the impact of xenobiotic exposure on MRP2 expression and transport function (Maher et al, 2005;Miller, 2010;Wang et al, 2014). However, to our knowledge no study has been conducted exploring the signaling mechanisms of disease-associated MRP2 regulation on a cellular level.…”
Section: Glutamate Upregulates Mrp2mentioning
confidence: 99%